セールロンダーネ サンチ チュウオウブ ニオケル ヒョウガ ノ キバン チケイ ヒョウガ オウダン チケイ ト ケイタイ カイセキ - Pattyn, Frank; Decleir, Hugo (1995)
P(論文) 本論では, セールロンダーネ山地中央部で実施した氷河の基盤地形観測のすべてを概観する。データは重力計法と電波探査法によるもので, この地域で以前に行われたベルギー隊およびJARE-28,-32の観測で得られた氷河の横断方向, 縦断方向のプロファイルである。こうしたデータを基に, この地域の氷河の基盤地形をまとめた。さらに, 氷河横断基盤形状の形態学的特徴の解析方法を示すが, この方法はこれまでのべき級数法則よりも良い結果をもたらした。最後に, 氷河横断基盤形状の本解析は, 現在の基盤地形が氷河の削剥能力と関連した複雑な地形発達過程にあることを明らかにした。 In this paper an overview is given of all subglacial topography measurements carried out in the central S∅r Rondane Mountains. Data of glacier valley cross and longitudinal profiles were gathered by gravimeter and radio echo sounding measurements during former Belgian expeditions and during the Japanese Antarctic Research Expeditions JARE-28 and JARE-32. Based on these data, a map of the subglacial topography in the central mountain area was compiled. Furthermore, a method is presented for analysing the morphometric characteristics of valley glacier cross profiles, which is shown to give beteer results than former power law equations. Finally, the morphometric analysis of the present glacierized valley cross profiles revealed a complex development regime, linked with the erosion potential of the glacierized area. departmental bulletin paper